Qualidade das madeiras de acácia e eucalipto provenientes de cultivo misto visando a produção de celulose - São Teago, Gilson Barbosa (2012)
The pulp and paper sector have great importance in Brazilian economy and their main sources of fiber are the forests of eucalypt and pine. Thus, it is strategic to research alternative fiber sources that might in the future make mixtures with eucalypt or even replace it. Acacia mangium has been used with good yield and quality of pulp and might be used an alternative source of fiber in simple or mixed stands. However, the literature lacks studies about the influence of mixed cultures on the properties of wood. In this way, this study aimed to evaluate the properties of wood of A. mangium and an eucalypt hybrid, both six years old, planted in monoculture and mixed stands in different proportions of the Rio Doce Valley, Minas Gerais state, Brazil. Were evaluated the specific gravity and content of bark, heartwood and sapwood, both along the stem, the radial variability of the vessels and fibers in three positions of DBH and chemical properties in DBH. For the acacia timber the results show a tendency to increase the content of sapwood with increasing proportion of A. mangium in the mixed stand; higher levels of bark at the base and top of the stem, higher specific gravity values at the base of the trunk, decreasing to 25% of commercial height and remaining constant up to the top; basic density of the tree is not influenced by treatments, for chemical properties, only the soluble lignin was influenced by the treatments; medium size vessels, few in number and with increasing diameter from pith to bark, fibers with thin walls and length ranging from very short to short in length and wall thickness increasing and the width and thickness of the heat decreasing from pith to bark. For the wood of the hybrid, results indicated decreasing levels of bark from the base to half the trunk and returning to climb to the top, higher specific gravity values for tree planting in treatments simple and longitudinal variation of this property with no defined pattern; tendency to occur higher lignin content and lower extractives content in the treatments in monoculture, small vessels and few in number with smaller vessel sizes in the treatments in monoculture and increase in vessel diameter from pith to bark, fibers with thick walls and lengths ranging from very short to short, the length, width and wall thickness of the fibers increased from pith to bark